The effect of Zn doping on the structure, phase transformation and electric properties of 0.5BZT-0.5BCT materials - Huang, Ling (Heliyon, 2024)
In the current study, an improved method of adding Zn ion doping to the 0.5BZT–0.5BCT–based films with high pyroelectric properties was designed. Under different Zn ion doping ratios, the structure, dielectric constant, phase transition relationship and other characteristics of the test product were analyzed experimentally to obtain the optimal ratio parameters. The experimental results demonstrate that the dielectric properties of the 0.5BZT–0.5BCT–xZn–based films proposed in this study can be far superior to those of other films under the optimal preparation process. The optimal dielectric properties and ferroelectric properties are obtained when the doped data are 0.008. Considering the comprehensive dielectric and energy storage capacity, the optimal doping ratio is 0.01, which can take into account dielectric data and energy storage performance. The energy storage density is 1.842 J/cm3, and the energy storage efficiency exceeds 30%. From 0 to 0.02, the properties of the material, such as the hysteresis loop and phase transition relationship are excellent. The properties of the materials studied in this study are excellent, and they are excellent candidate materials for the future application of ferroelectric materials, and provide ideas for related work.